Novel Mutations in MLH1 and MSH2 Genes in Mexican Patients with Lynch Syndrome - Jose Miguel Moreno-Ortiz; María de la Luz Ayala-Madrigal; Jorge Román Corona-Rivera; Manuel Centeno-Flores; Víctor Maciel-Gutiérrez; Ramón Antonio Franco-Topete; Juan Armendáriz-Borunda; Erin Hotchkiss; Lucia Pérez-Carbonell; Jennifer Rhees; Clement Richard Boland; Melva Gutiérrez-Angulo (Gastroenterology Research and Practice)
Background. Lynch Syndrome (LS) is characterized by germline mutations in the DNA mismatch repair (MMR) genes MLH1, MSH2, MSH6, and PMS2. This syndrome is inherited in an autosomal dominant pattern and is characterized by early onset colorectal cancer (CRC) and extracolonic tumors. The aim of this study was to identify mutations in MMR genes in three Mexican patients with LS. Methods. Immunohistochemical analysis was performed as a prescreening method to identify absent protein expression. PCR, Denaturing High Performance Liquid Chromatography (dHPLC), and Sanger sequencing complemented the analysis. Results. Two samples showed the absence of nuclear staining for MLH1 and one sample showed loss of nuclear staining for MSH2. The mutations found in MLH1 gene were c.2103+1G>C in intron 18 and compound heterozygous mutants c.1852_1854delAAG (p.K618del) and c.1852_1853delinsGC (p.K618A) in exon 16. In the MSH2 gene, we identified mutation c.638dupT (p.L213fs) in exon 3. Conclusions. This is the first report of mutations in MMR genes in Mexican patients with LS and these appear to be novel.